Protecção de dados pessoais na internet - Duarte, Vânia Sofia António (2016)
The present dissertation has as object of study the right to be forgotten, a new right for increase the control of subject over their data. It’s analyzed the data protection on Internet, especially, some scenarios of processing and the regulation applicable to it (directive 95/46/CE and directive 2002/58/CE).